Prevalence, Causes, and Risk Factors of Visual Impairment in Emiratis and Non-Emiratis of Dubai: A Subnational Population-Based Cross-Sectional Survey. (30th April 2022) - Taryam, Manal O.; Rabiu, M. Mansur; AlBanna, Shurooq; Al Shamsi, Noora; Albastaki, Bushra; Khan, Hayat; Chettiankandi, Salam; Alnakhi, Wafa Khamis; Hussain, Hamid Y.; Rao, Prasan; Singh, Gurdeep; Pai, Sivakami; et al.
Abstract : Purpose . To study the prevalence, causes, and risk factors of visual impairment (VI) among the Dubai Emiratis and non-Emiratis. Methods . The survey was a population-based cross-sectional eye health study conducted 2019-2020. Cluster sampling was used to randomly select local (Emirati) and expatriate (non-Emirati) Dubai residents aged 40 years and older. Ocular examinations were conducted in selected eye clinics to determine the visual acuity (VA) and cause(s) of VI if any. Trained nurses, optometrists, and ophthalmologists did the examinations. VA was measured using ETDRS visual chart. The World Health Organization VI and blindness definitions and classifications for the cause(s) of VI were used. Results . A total of 892 participants were included in the final analysis. The mean age [SD] was 52.09 [9.48] years, with 55.8% as males. Prevalence of presenting mild, moderate, and severe VI was 4.7% (2.94–7.11%), 1.8% (0.78–3.5%), and 0% for Emiratis, and 3.6% (2.06–5.76), 1.6% (0.63–3.21), and 0% for non-Emiratis, respectively. Four Emirati participants were blind, with a prevalence of 0.9% (0.25%–2.28%). Men had lower likelihood of VI than women (odds ratio [OR] (95% CI): 0.42 (0.24–0.77)) after adjustment for covariates. Diabetes (OR (95% CI): 1.91 (1.04–3.52)) was an independent risk factor for VI. Higher education level was associated with a lower likelihood of VI (OR (95% CI): 0.34 (0.13–0.89). Leading causes of VI among Emiratis were uncorrected refractive error (52%) and cataract (17.2%). Glaucoma, optic atrophy, and absent globe were the causes of blindness. Conclusions . Prevalence of VI is comparably low with leading causes readily treatable. An effective strategy to improve spectacle correction and cataract services would reduce the VI burden.